2007
DOI: 10.1128/jvi.02203-06
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Mutations in the Connection and RNase H Domains of Human Immunodeficiency Virus Type 1 Reverse Transcriptase That Increase Resistance to 3′-Azido-3′-Dideoxythymidine

Abstract: Recent work indicates that mutations in the C-terminal domains of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) increase 3′-azido-3′-dideoxythymidine (AZT) resistance. Because it is not known whether AZT selects for mutations outside of the polymerase domain of RT, we carried out in vitro experiments in which HIV-1LAI or AZT-resistant HIV-1LAI (M41L/L210W/T215Y) was passaged in MT-2 cells in increasing concentrations of AZT. The first resistance mutations to appear in HIV-1LAI were two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 35 publications
7
85
0
Order By: Relevance
“…Our data support the functional equivalence of the ⌬67/T69G/K70R complex and the double mutation D67N/K70R. Previously reported phenotypic data showed that D67N/K70R confers 4.6-fold and 1.4-fold increased resistance to AZT and d4T, respectively (44). These values are similar to those found in our study for HIV-1 bearing the ⌬67/T69G/K70R RT.…”
Section: Discussionsupporting
confidence: 81%
“…Our data support the functional equivalence of the ⌬67/T69G/K70R complex and the double mutation D67N/K70R. Previously reported phenotypic data showed that D67N/K70R confers 4.6-fold and 1.4-fold increased resistance to AZT and d4T, respectively (44). These values are similar to those found in our study for HIV-1 bearing the ⌬67/T69G/K70R RT.…”
Section: Discussionsupporting
confidence: 81%
“…Clinical data obtained from Canadian (26) (this study) and Brazilian cohorts (25) suggest that N348I can appear early in therapy, independently of preselected TAMs, whereas A360V appears late following the emergence of TAMs. It has been proposed that connection domain mutations exert their effects on excision indirectly through alterations in RNase H cleavage (26,28,32,33). Here we asked how the two connection domain mutations can affect RNase H cleavage and whether such changes are necessary and sufficient to cause an increase in phosphorolytic excision of AZT-MP.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, many of these mutations, including mutations N348I, A360I/V, and A371V, in the connection domain of HIV-1 RT were identified in clinical samples of HIV-infected individuals. In addition, A371V and Q509L in the RNase H domain emerge under the selective pressure of AZT in cell culture (28). The rare G333D/E polymorphisms have been associated with dual resistance to AZT and other NRTIs (29,30), and few connection mutations, including Y318F and N348I, have been linked to decreased susceptibility to NNRTIs (23,26,31).…”
mentioning
confidence: 99%
“…Mutations considered were N348I, A360V, T369I/V, A371V, A376S, A400T, D488E, Q509L, and Q547K for their recognized phenotypic role in drug resistance. [34][35][36][37][38] For the discovery of novel HIV-1C mutations associated with drug exposure, RT C-terminal sequences of this subtype were compared to global and Brazilian HIV-1C sequences from drug-naive subjects. Global consensus was obtained from the Los Alamos database, whereas the Brazilian consensus was inferred using sequences obtained from this study and additional 91 HIV-1C sequences of CN and 115 of RNH recently described by our group.…”
Section: Sequence and Phylogenetic Analysesmentioning
confidence: 99%